KONDISI UDARA PADA AREA KERJA PABRIK TAHU HARAPAN MAJU DEPOK, JAWA BARAT - Yulianti, Ririn; Nuryana, Suherman Dwi; Hartami, Pantjanita Novi; Budhya, Emmy Fatmi; Sari, Sekar Tika (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
The temperature of the human body is strongly influenced by the working climate of its environment. A high-pressure work environment will certainly have an influence on the worker's body temperature and make a separate burden for workers in a work environment. Humans have the ability to adapt in colder and hotter environments with certain restrictions. The consequences that occur when a person does physical activity in a hot temperature place is not only affected by the decrease in achievement of his activity but also increases the risk of developing diseases caused by hot temperatures. Workers who are exposed to hot temperatures continuously can cause dehydration to hyperthermia. In the tofu industry, there is a process of grinding and cooking of course using tools that will be a source of heat in the work environment. The purpose of this Community Service (PKM) is to provide information to factory industry owners and workers to know about the air conditions at the work site and how the time allowed to work so as not to cause comfort and health disruption for workers. The implementation method is carried out by conducting surveys, data retrieval and socialization hybridly. After the community service activities, managers and Harapan Maju Tofu Industrial workers to know the working climate conditions in their work environment so as to create safe and comfortable working conditions